2010
DOI: 10.1007/s11011-010-9210-1
|View full text |Cite
|
Sign up to set email alerts
|

Saccadic latency in hepatic encephalopathy: a pilot study

Abstract: Hepatic encephalopathy is a common complication of cirrhosis. The degree of neuro-psychiatric impairment is highly variable and its clinical staging subjective. We investigated whether eye movement response times—saccadic latencies—could serve as an indicator of encephalopathy. We studied the association between saccadic latency, liver function and paper- and pencil tests in 70 patients with cirrhosis and 31 patients after liver transplantation. The tests included the porto-systemic encephalopathy (PSE-) test,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 45 publications
2
6
0
Order By: Relevance
“…Moreover, it is comparatively rapid, taking only 7 min to gain a data set, and requires no specialist training or personnel to administer. We have shown that an assessment of a patient's saccades correlates strongly with psychometric performance, an observation in line with those made by Krismer et al (Krismer et al 2010).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, it is comparatively rapid, taking only 7 min to gain a data set, and requires no specialist training or personnel to administer. We have shown that an assessment of a patient's saccades correlates strongly with psychometric performance, an observation in line with those made by Krismer et al (Krismer et al 2010).…”
Section: Discussionsupporting
confidence: 89%
“…Finally, previous studies have demonstrated that HE affects eye movements. Smooth pursuit eye movements are disrupted in conjunction with the degree of encephalopathy (Montagnese 2005), and a recent pilot study using saccadometry has shown increased saccadic latency in HE, correlating both with psychometric tests and flicker fusion performance (Krismer et al 2010). We therefore investigated whether the measurement of saccades might provide a novel quantitative neurological assessment for the diagnosis of CHE.…”
Section: Introductionmentioning
confidence: 99%
“…The LATER model is a robust and simple way to model the RT distribution of saccades, and it was successfully applied to provide a quantitative measure of the RT distribution differences in patients with a variety of neurological disorders (Antoniades et al, 2010(Antoniades et al, , 2012Chandna, Chandrasekharan, Ramesh, & Carpenter, 2012;Krismer et al, 2010;Perneczky et al, 2011).…”
mentioning
confidence: 99%
“…Prior to any data analysis, incorrect trials were filtered out and removed. Saccades with a latency less than 50 ms were excluded, in line with other saccade research (Krismer et al 2010;Knox, Wolohan & Helmy 2017;Amatya, Gong & Knox 2011). Saccades with latencies this low are generated too fast to be a response to the visual stimulus and are classed as anticipatory.…”
Section: Discussionmentioning
confidence: 99%